Exposure to thin and non-thin bodies elicits 'feeling fat': Validation of a novel state measure. (January 2023) - Wilson, Samantha; Mehak, Adrienne; Racine, Sarah E.
Abstract: 'Feeling fat' refers to the subjective experience of carrying excess weight and relates to severity of eating pathology. Despite research suggesting that 'feeling fat' fluctuates across contexts, this construct is almost exclusively assessed in terms of frequency or as a trait. Examining state 'feeling fat' in response to external stimuli can inform us of the nature of this construct. In an experimental study, 290 community women were exposed to five categories of affective (pleasant, aversive, and neutral) and body (thin and non-thin) images in quasi-random order. Self-Assessment Manikin (SAM) valence and arousal rating scales as well as a novel SAM 'feeling fat' scale were rated for each image. Theoretically-relevant constructs (i.e., trait 'feeling fat', thin-ideal internalization, body dissatisfaction, eating pathology) were also measured. Body images elicited greater state 'feeling fat' than affective images, with images of non-thin bodies producing higher state 'feeling fat' than thin bodies. Positive correlations were observed between state 'feeling fat' in response to thin and all variables of interest, whereas associations between these variables and 'feeling fat' in response to non-thin images were small or non-significant. The development of a state measure of 'feeling fat' allows for the investigation of triggers of this bodily experience and will facilitate future research. Highlights: 'Feeling fat' is greater in response to body images than to affective images. Images of non-thin bodies elicited the strongest 'feeling fat'. Relations between 'feeling fat' and external variables differ by body image type. The Self-Assessment Manikin (SAM) 'feeling fat' scale is a valid state measure. SAM 'feeling fat' scale captures fluctuations in this bodily experience.